If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (z + 5)(z + -8) = -3(z + 8) Reorder the terms: (5 + z)(z + -8) = -3(z + 8) Reorder the terms: (5 + z)(-8 + z) = -3(z + 8) Multiply (5 + z) * (-8 + z) (5(-8 + z) + z(-8 + z)) = -3(z + 8) ((-8 * 5 + z * 5) + z(-8 + z)) = -3(z + 8) ((-40 + 5z) + z(-8 + z)) = -3(z + 8) (-40 + 5z + (-8 * z + z * z)) = -3(z + 8) (-40 + 5z + (-8z + z2)) = -3(z + 8) Combine like terms: 5z + -8z = -3z (-40 + -3z + z2) = -3(z + 8) Reorder the terms: -40 + -3z + z2 = -3(8 + z) -40 + -3z + z2 = (8 * -3 + z * -3) -40 + -3z + z2 = (-24 + -3z) Add '3z' to each side of the equation. -40 + -3z + 3z + z2 = -24 + -3z + 3z Combine like terms: -3z + 3z = 0 -40 + 0 + z2 = -24 + -3z + 3z -40 + z2 = -24 + -3z + 3z Combine like terms: -3z + 3z = 0 -40 + z2 = -24 + 0 -40 + z2 = -24 Solving -40 + z2 = -24 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '40' to each side of the equation. -40 + 40 + z2 = -24 + 40 Combine like terms: -40 + 40 = 0 0 + z2 = -24 + 40 z2 = -24 + 40 Combine like terms: -24 + 40 = 16 z2 = 16 Simplifying z2 = 16 Take the square root of each side: z = {-4, 4}
| 10-15x=22 | | 14x(x-4)=5(9-22x)+9x(x+6) | | 2g-m=5-gh | | 4x^3=5.5 | | 4x+5-7=26 | | -(8x+8)=-72 | | -2(6x-5)=46 | | 4x^2+5x+6=0 | | 9y^2+19=30y | | -x^2-198=0 | | 27p^3-108pq^3=0 | | x^2+18+76=0 | | -19=8-3(-2k-3) | | x+y=1300 | | 3(1-x)=24 | | -16h=8(2h-10) | | 6a^2-6=0 | | 6b=-42-b | | 0=a^2+12a+32 | | 2m^3=7 | | 3x-(5x-3)=26 | | ln(x-2)-ln(x+3)=ln(x-1)-ln(x+7) | | -7(a-8)=7 | | 7s^2-19st+10t^2=0 | | 12x^5-11x^7+15x^8=0 | | 9x-7y=8 | | 6q=24q+6 | | x+(x+6)=4 | | 41-q=3q-15 | | 5-2p=6*q+1 | | 28+y=90 | | f(-11.9)=[-11.9+.5]-3 |